The use of gravity model in spatial planning - Kurowska, Krystyna; Kryszk, Hubert; Kietlinska, Ewa (International Conference “Environmental Engineering”, 2017)
The GIS tools facilitate organised and formal creation of models presenting both the current state of and the forecasted changes in physical environment (ones that will occur if specific conditions are satisfied). Formulated in 1962, D. L. Huff’s algorithm is gaining in popularity nowadays; it helps determine the probability of a particular venue being chosen from amongst several competitive ones. Initially, it was used to define the optimal location of new points of sale; but with the technological progress of the GIS and with an increased demand for studies on distribution of venues or service points, its scope of use in urban planning is becoming more and more extensive. The results of the study support decision-making processes and are invaluable help in selection of optimal locations. This article presents how Huff’s algorithm and Lakshmanan-Hansen’s channel pass-through model can be used in physical planning of cities with the focus on new trade centres. The research was based on the case study of Warsaw – the biggest city in Poland. The analysis conducted showed not only what market share particular centres had, but it also demonstrated what changes could be expected upon appearance of new trade centres.